Judy Moody and the NOT Bummer Summer [anglicky] / Book 10. - McDonald, Megan 1959- (Walker Books Ltd, 2019)
It’s bad enough that Mum and Dad are heading to California, leaving Judy and Stink with Aunt Awful (er, Opal), but now Judy’s two best friends are going splitsville on her too. Just when it looks like her summer is going to be boring-with-a-capital B, eureka! Judy (with some help from Aunt Opal) comes up with the most thrill-a-delic plan ever. Get ready for tightrope walking, roller coaster riding, a treasure hunt to find Judy's teacher, a midnight stakeout, a runaway ice-cream truck and a hunt for Bigfoot.